Alcohol acetylation with acetic acid using borated zirconia as catalyst - Blanco, Mirta Noemi (2009)
The use of zirconium oxide doped with boron (borated zirconia) as catalyst in the acetylation of alcohols and phenol was studied. The catalysts were obtained by employing different preparation conditions, in order to observe the effect of the concentration of the precursor in the solution used to obtain the oxide, the concentration of the boron precursor, and the calcination temperature. All the solids showed amorphous characteristics and strong acidity. Boron addition increased the temperature range of the hydrated oxide stability, which depends on the boron concentration in the sample. Besides, the characterization by infrared spectroscopy showed an effect on the boron species present in the solid depending on the added concentration. The three preparation conditions under study affected the textural properties of the catalysts, as well as their acid strength. It was observed that in the acylation of alcohols using acetic acid as acylating agent and toluene as reaction solvent, at reflux temperature, the yield of acetylated product correlated with the acid strength of the catalysts, which depended on the preparation conditions. The best yield was achieved with a catalyst obtained using a high solution concentration of the oxide precursor (0.56 mmoles Zr/cm3), an intermediate boron concentration (15 g B2O3/100 g support) and a relatively low calcination temperature (320ºC).